Prototype Solar Tracker based on two Arduino Nano Microcontroller with LDR (Light Dependent Resistor) sensor - Jhefri Asmi; Oriza Candra (STEKOM PRESS, 2020)
The community's need for electricity is getting higher, so alternative energy sources such as solar heat are needed to replace energy sources from fossil fuels in meeting electricity needs. In this paper we design a two-axis solar tracker with an LDR sensor. A sun tracking system is a unit that is combined into one to control the position of the tracking device with the aim of making the surface of the solar panel module always facing the direction of sunlight. This research discusses the Prototype of the Sun Tracking System in Arduino Based Solar Power Generation Systems to get maximum solar energy. This system will make solar panels move automatically so that sunlight absorption can be maximized. The main control uses Arduino nano which gets input values ​​from the LDR sensor then is processed to the output system. With the control system method can automatically be seen the difference in the results of a fixed solar panel with a solar panel with a tracker, from the comparison we get a solar panel with a tracker to get more optimal results.